A review of Data Development Analysis (DEA) applications in supply chain management research - Woramol Chaowarat (2018)
© 2013 IEEE. The objective of this paper is to review the application of Data Envelopment Analysis (DEA) in Supply Chain Management (SCM) research including different perspectives and research topics. In this review, academic databases used were ScienceDirect, Scopus and Google Scholar. The latter database was included to identify unpublished studies, conference proceedings and other types of unpublished studies. Practical review criteria are used for the inclusion or exclusion of the pertinent literature. In total 55 publications were found and analyzed in this paper. We found that even though both DEA and SCM were established as a field of study for a long time but there are only a few that applied the DEA to SCM. Most of studies applying DEA in SCM did not consider the whole supply chain, only some parts of the chain were analyzed. Based on the findings of the review, potential research agendas were developed.